933 FACTORS ASSOCIATED WITH LENGTH OF STAY ON OLDER PEOPLE'S MEDICINE WARDS. (14th June 2022) - Bunn, J; Lewis, E G; Cropp, A; Baldwin,; Wilson, C; Frith, J; Kilsby, A
Abstract: Introduction: The Newcastle upon Tyne Hospitals NHS Foundation Trust's Older People's Medicine (OPM) department includes six inpatient wards. It was hypothesized that an increasing prevalence of inpatient frailty would be associated with increased length of stay. Method: Data were collected on OPM wards, on a single day of February 2020 and July 2021. Demographic details, mobility, presence of delirium, resuscitation status, length of stay (LOS), and Clinical Frailty Scale (CFS) status was recorded (frailty defined as CFS score ≥ 5). Descriptive statistics and tests of significance comparing 2020 with 2021 data were performed. Independent associations with above-median LOS were analysed using binary logistic regression. Results: There were 172 inpatients in 2020, and 160 in 2021. Median age was 84 (range 66–98 years) in 2020, and 85 (range 64–99 years) in 2021. 87 (54.4%) in 2021, and 102 (59.3%) in 2020 were female. Prevalence of pre-admission frailty was higher in 2021 (n = 143, 89.4%) compared to 2020 (n = 125, 72.7%, p < 0.0001). The prevalence of delirium was higher (n = 60, 37.5%, p < 0.0001) and fewer were independently mobile (n = 53, 33.1%, p = 0.013) in 2021 than in 2020. Nevertheless, median LOS was shorter in 2021, 9 days (range 1.0–106.9) versus 15 days (range 0.7–87.0) in 2020, p = 0.006. Being admitted from home and having a DNACPR were independent predictors of increased LOS (OR 2.4 [95% CI 1.4 to 4.0] for both), controlling for age, sex, frailty, delirium, and reduced mobility. Conclusion: Despite the increased prevalence of frailty, delirium and reduced mobility, these factors were not associated with increased LOS. Residence at home and DNACPR were associated with above-median LOS, irrespective of the patient's frailty, delirium or mobility status. Overall, this suggest appropriate high quality care is being delivered, despite increased pressures due to shorter LOS and higher frailty prevalence.